The Design of Digital Liquid Density Meter Based on Arduino - Megantoro, Prisma; Widjanarko, Andrei; Rahim, Robbi; Kunal, Kunal; Zuhri Arfianto, Afif (Universitas Muhammadiyah Yogyakarta, 2020)
A measure of liquid thickness is needed to make a dough or formula for medicinal syrup. The tools to measure the thickness available in the market are analog that is less accurate and precision. To overcome these problems, digital density measuring devices are needed. The limitation of the digital density meter, especially liquid, urges the author to carry out further research on the digitization of this measuring instrument. This research aims to make a digital density meter for liquid matter with a high level of measurement accuracy, as the reference measurement study for liquid density in digital form. The instrument was designed using the load cell method as the main sensor. It was also equipped with a DS18B20 water-resistant temperature sensor to measure the temperature of the liquid. The data were analyzed to obtain the accuracy and error of the liquid density measurement from the density meter. The liquid samples used for research were Pertamax, solar, and water. Sample accuracy and error measurement results were 99.83 percent and 0.17 percent respectively for Pertamax, 99.63 percent and 0.37 percent for solar and 99.46 percent and 0.54 percent for water. The measured density value was finally shown on the 16x2 LCD.